The effects of the CEECS's accession on sectoral trade: A value added perspective - Lennart C. Kaplan; Tristan Kohl; Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
International fragmentation of production and economic integration change the structure of international trade. Novel datasets reveal how production processes are unbundled across borders and connected internationally through Global Value Chains (GVCs). Yet, the impact of Economic Integration Agreements (EIAs) on GVCs is still poorly understood. This paper investigates how the accession of 10 Central and Eastern European Countries (CEECs) to the European Union (EU) affected trade in value added in Europe. Using a gravity model of international trade for a sample of 40 countries over the period 1995-2009, we find that EU accession mainly fostered Eastern entrants' integration in other CEECs' value chains. Smaller integration benefits arise for East-West trade in services stemming from low-skill value adding activities.
Keywords: F13; F15; 330; economic integration; international fragmentation; gravity model; European Union